Usandsynligheder, overkrydsninger og umuligheder. En retorisk tilgang til brud på den mimetiske karakternarrations kode - Phelan, James (K&K - Kultur og Klasse, 2011)
IMPROBABILITIES, CROSSOVERS, AND IMPOSSIBILITIES | Extending and to some extent revising some of his earlier work, James Phelan in this essay examines three kinds of “unnatural” departures from the mimetic code. Paralepsis (or implausible knowledgeable narration), simultaneous present-tense character narration, and a kind of departure not previously noticed, which he calls cross over narration: “an author links the narration of two independent sets of events by transferring the effects of the narration of the one to the other.” In spite of being rather different ways of breaching the mimetic code, the three breaks form a useful cluster for investigating underlying conventions of reading that can explain why readers often do not notice the breakes. Phelan thus induces two Meta-Rules of Readerly Engagement: The Value Added Meta-Rule underlies the principle that disclosure functions trump narrator functions, and stipulates that readers overlook breaks in the mimetic code when those breaks enhance their reading experience; the Story over Discourse Meta-Rule stipulates that once a narrative foregrounds its mimetic component, readers will privilege story elements over discourse elements, and thus be inclined to overlook breaks in the code. Four additional Rules are derived from the Meta-Rules in a reading of Adventures of Huckleberry Finn, which serves as an example of implausibly knowledgeable narration. Rules and Meta-Rules are then deployed in reading a passage of The Great Gatsby, exemplifying crossover narration. A discussion with Henrik Skov Nielsen about the simultaneous present-tense narration in Glamorama marks both the closeness and a certain difference in perspective between rhetorical narratology and Nielsen’s concept of narration without narrators.